Review for High Frequency Propagation Wave Through the Ionosphere Based on IRI Model Using Ray-Tracing Technique - Fatima Hikmat Ali; A.J. Stocker; Hasanain Abbas Hasan Al-Behadili; Nsaif Jasim Hadi (Misan Journal of Engineering Sciences)
The ionosphere's condition affects how HF radio waves propagate, which changes over time of day, season, and Solar activity conditions. These waves, when propagating through ions, are affected by several factors, including refraction, reflection, and absorption. To reduce these effects, ray tracing is an important tool that depends on atmospheric communication, relying on the IRI model to describe the ionosphere's parameters. This paper is an overview of the ionosphere and reviews the IRI model and ray tracing technique. IRI is acknowledged as the ionosphere's official standard by the organization for international standards, International Radio Science Union, Europe's collaboration with the Space Research Committee to promote space. According to these organizations, the IRI is a pilot (data-based) model that represents the basic parameters of the ionosphere based on the ion cover data record.